Environmental heterogeneity: Anuran diversity in homogeneous environments - Silva, Rodrigo Augusto [UNESP]; Martins, Itamar Alves; Rossa-Feres, Denise de C. [UNESP] (Sociedade Brasileira de Zoologia, 2011)
The northwestern region of São Paulo was extensively deforested during the agricultural expansion in the last century and only small fragments of the original vegetation cover remained. In this study, we investigated how habitat features influence the composition, richness, and diversity of anurans in environments homogenized by agricultural activities. We sampled monthly six breeding ponds located in pasture areas during twelve months. We recorded ten environmental descriptors for each breeding pond. We found 18 anuran species. The breeding ponds were structurally similar, but species composition differed among them. The environmental descriptors influence varies for each species, as demonstrated by the different associations between species and environmental descriptors shown in the Canonical Correspondence Analysis (CCA). Seven of the ten environmental descriptors explained 67% of the species richness, showing that environmental characteristics influenced the occurrence of the different species. There is no such data set for the region and also for most Brazilian regions, despite its importance in guiding species-oriented conservation actions.
Keywords: Amphibia; Community ecology; environmental indicators; habitat use; beta diversity